Cardiac Intimal Sarcoma with Complete Response to Thoracic Radiotherapy- A Case Report - Aurelia, Alati; Valerie, Le Brun-Ly; Sophie, Leobon; Isabelle, Pommepuy; Romain, Turcat; Helene, Orliac; Pierre, Clavere (Archives of Clinical and Medical Case Reports, 2020)
Objectives: Sarcomas are the most common primary, cardiac malignant tumours but are, nevertheless, rare (0.001-0.03% of all tumours [1-4]. Intimal sarcomas characterised by Murine Double Minute 2 (MDM2) gene amplification originate from large vessels, but from the heart only very rarely. The prognosis of primary cardiac sarcomas is very poor; no evidence-based management guidelines are available. Surgery is the first-line treatment but is not possible in over 50% of cases. Radiotherapy ensures efficient local control and is indicated as neoadjuvant, adjuvant, and palliative treatment. Materials and Methods: We report the case of a 59-year-old female with a metastatic, cardiac intimal sarcoma identified after symptomatic metastasis to the lower limbs. Imaging revealed a hypermetabolic cardiac mass emerging from the left atrium. Adductor muscle biopsy identified an intimal sarcoma metastasis exhibiting MDM2 gene amplification; the primary site was cardiac. We first prescribed anthracycline chemotherapy and irradiation of the cardiac mass. She received 50 Gy into the planned target volume including the atrial mass (2 Gy per day 5 days per week) delivered via three-dimensional external-beam radiotherapy. Results: The irradiated cardiac mass did not grow during follow-up, rather, stabilising and then gradually decreasing in size, associated with reduced hypermetabolism. Seven months after radiotherapy ceased, she achieved a complete cardiac response, but the metastatic lesions progressed. Her general condition improved. The heart failure signs disappeared and her symptoms became less serious. Conclusion: Radiotherapy should be favoured for patients with cardiac or intimal sarcomas featuring MDM2 amplification. The tumour seems to be radiosensitive, although anthracycline may also have been helpful. Radiotherapy is a valuable tool an